2016
DOI: 10.1007/s00203-016-1279-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of charged amino acid substitution in the transmembrane domain of l-alanine exporter, AlaE, of Escherichia coli on the l-alanine export

Abstract: The Escherichia coli alaE gene encodes the L-alanine exporter, AlaE, that catalyzes active export of L-alanine using proton electrochemical potential. The transporter comprises only 149 amino acid residues and four predicted transmembrane domains (TMs), which contain three charged amino acid residues. The AlaE-deficient L-alanine non-metabolizing cells (ΔalaE cells) appeared hypersusceptible to L-alanyl-L-alanine showing a minimum inhibitory concentration (MIC) of 2.5 µg/ml for the dipeptide due to a toxic acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Thus, YgaW is likely to be the physiologically most relevant exporter for L-alanine in E. coli. More recently, two charged residues (R45 and D84) were found to be essential for AlaE efflux activity [19].…”
Section: Plos Onementioning
confidence: 99%
“…Thus, YgaW is likely to be the physiologically most relevant exporter for L-alanine in E. coli. More recently, two charged residues (R45 and D84) were found to be essential for AlaE efflux activity [19].…”
Section: Plos Onementioning
confidence: 99%
“…These results indicated that the C-terminus of AlaE is localized in the cytoplasm of the cells. Next, we used a cysteine-less AlaE variant, which retained l -alanine export activity [20], to construct single Cys variants (V12C, Q40C, S41C, S76C, W107C and A149C); the amino acid residues involved in these substitutions were predicted to be localized in the aqueous phase of the cytoplasm and periplasm. When cells are first treated with MTSET, a non-fluorescent reagent, followed by fluorescent OGM treatment as described in the Methods, cysteine residues present in the cytoplasm are supposed to be labelled with OGM.…”
Section: Resultsmentioning
confidence: 99%
“…Certain transmembranes of AlaE were predicted to be involved in the oligomerization step. In our earlier random mutagenesis study, four AlaE missense mutations (S34F, S116L, G125E and G129D) were identified in the TM helices, each of which leads to the dysfunction of AlaE [20]. Interestingly, three (S116L, G125E and G129D) amino acid changes among them were present in the TM4, implying that TM4 plays an important role in AlaE function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations